2021
DOI: 10.1186/s12906-021-03369-0
|View full text |Cite
|
Sign up to set email alerts
|

Piperlongumine inhibits migration and proliferation of castration-resistant prostate cancer cells via triggering persistent DNA damage

Abstract: Background Metastatic castration-resistant prostate cancer (CRPC) is the leading cause of death among men diagnosed with prostate cancer. Piperlongumine (PL) is a novel potential anticancer agent that has been demonstrated to exhibit anticancer efficacy against prostate cancer cells. However, the effects of PL on DNA damage and repair against CRPC have remained unclear. The aim of this study was to further explore the anticancer activity and mechanisms of action of PL against CRPC in terms of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In their study, Zhang et al [ 82 ] explored the anticancer activity and mechanisms of action of PL against CRPC in terms of DNA damage and repair processes and demonstrated that PL has an IC 50 of 6.75, 8.42, 8.73, and 68.62 μM in PC3 cells, DU145 cells (cells that are derived from bone and brain metastasis of CRPC), WPMY-1 cells, and LO2 cells. The results showed that PL exhibits anticancer activity in a dose-dependent manner (1, 2, and 4 μM) and is stronger against CRPC cells compared to taxol, cisplatin (DDP), doxorubicin (Dox), or 5-fluorouracil (5-FU), with fewer side effects in normal cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, Zhang et al [ 82 ] explored the anticancer activity and mechanisms of action of PL against CRPC in terms of DNA damage and repair processes and demonstrated that PL has an IC 50 of 6.75, 8.42, 8.73, and 68.62 μM in PC3 cells, DU145 cells (cells that are derived from bone and brain metastasis of CRPC), WPMY-1 cells, and LO2 cells. The results showed that PL exhibits anticancer activity in a dose-dependent manner (1, 2, and 4 μM) and is stronger against CRPC cells compared to taxol, cisplatin (DDP), doxorubicin (Dox), or 5-fluorouracil (5-FU), with fewer side effects in normal cells.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, PL treatment (1, 2, and 4 μM) induced apoptosis in DU145 cells, with a concomitant increase in p53 expression. Finally, PL treatment triggered persistent DNA damage and caused strong DNA damage responses in CRPC cells [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study on lung cancer cells (A549 and NCI-H460) treated with 20 µ m PL for 24 h, DAPI staining revealed an increase in apoptotic bodies, demonstrating that PL induces apoptosis in lung cancer cells ( 40 ). Similarly, in PL (1, 2, and 4 µ m)-treated DU145 prostate cancer cells, Annexin V-PI staining reveals a dose-dependent increase in apoptosis ( 41 ). The aforementioned studies support the present findings that PL induced apoptosis in melanoma cells.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, piperlongumine was found to exhibit promise anti-cancer activities in various cancers. In castration-resistant prostate cancer cells, DNA could be damaged persistently by piperlongumine treatment to inhibit proliferation, migration, and invasion of prostate cancer cells [ 239 ]. Apoptosis and cell cycle arrest can also be induced by piperlongumine in gastric, cervical, and colorectal cancer cells [ 240 ].…”
Section: Phytochemicals Targeting Ros and Autophagy For Cancer Therapymentioning
confidence: 99%